Implementation of Post-Accreditation Administration and Management Group Recommendations at Candimulyo Health Center - Retno Mariani; Chriswardani Suryawati; Ayun Sriatmi (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
The implementation of the recommendations is a continuous improvement effort in improving the quality of Public Health Center services and is related to the strategy for increasing accreditation status. However, a preliminary study in Magelang District showed that the implementation of the follow-up recommendations given by the surveyor to the administration and management group was only carried out by the Candimulyo Health Center. This study aims to analyze the implementation of recommendations in the post-accreditation Administration and Management group at the Candimulyo Health Center, Magelang Regency. This research is a qualitative research with a case study research design. This research started from August to October 2022. There were 6 informants in this study consisting of the Head of the Public Health Center, the Admen in Charge, the Head of Quality and the Admen Team Members as the main informants. Data collection techniques in this study are in-depth interviews. Data validation uses source triangulation with informant triangulation. Analysis of the research data is data reduction, data presentation and drawing conclusions. The results showed that only 28% of the recommendations had been implemented. The administration and management team already exists but there are no standards regarding post-accreditation activities, no specific planning and no monitoring and evaluation mechanism. The implementation of the recommendations at the Candimulyo Health Center has not been optimal because there is no specific plan regarding follow-up and support from the health office through monitoring and evaluation. Further research is needed on factors related to the non-implementation of post-accreditation monitoring and evaluation at the health office level. it is advisable to make reference to post-assessment accreditation activities including planning for the implementation of recommendations. and it is advisable to develop a policy mechanism for monitoring the implementation of recommendations. Keywords: Accreditation, Quality, Recommendation